Clinical efficacy of Masquelet technique in the treatment of tibial and fibular bone defects caused by severe gunshot wounds - Qiming Sun; Yingjie Cong; Wei Sun; Xinwei Liu; Baolei Guo; Chunli Zhao; Baoxian Hou; Ye Liu; Dapeng Zhou (Frontiers in Medicine, 2026)
Objective To explore the clinical efficacy of the Masquelet technique in the treatment of tibial and fibular bone defects resulting from severe gunshot wounds. Methods A retrospective analysis was conducted on six male patients (mean age, 23 ± 5 years; range, 18 to 33 years) with tibial and fibular bone defects resulting from gunshot wounds, treated with the Masquelet technique between January 2022 and January 2024. In Stage 1, blood transfusions and fluid resuscitation were administered to manage shock. Wound debridement was performed, followed by applying an external fixator. The average length of the bone defects was 8.7 ± 2.2 cm (range, 5.4 to 12.3 cm). The bone defect areas were filled with vancomycin-loaded bone cement, and the wounds were closed using vacuum sealing drainage (VSD). In Stage 2, the bone cement device was surgically removed, and the external fixator was replaced with an intramedullary nail. Autologous iliac bone grafts in strip form were implanted in the induced membrane to manage the bone defects. Postoperatively, the wound healing and inflammatory indicators were observed to determine the infection control status. Regular X-ray examinations on the affected extremities were conducted to evaluate the bone healing status in the defect areas. Results The mean follow-up duration was 13.7 ± 0.9 months (range, 12 to 15 months). The interval between Stage 1 and Stage 2 ranged from 16 to 32 weeks (mean 22.7 ± 5.1 weeks). The number of debridement in Stage 1 varied from 2 to 3 times (mean 2.5 ± 0.5 times). All six patients underwent free flap transplantation for wound coverage, and the flaps healed well in all patients. Bone union was achieved in all six patients, and the healing time was 10 to 15 months (mean 12.5 ± 1.5 months). Callus formation was uniform in the bone defect areas, indicating successful bone union, and the fracture lines became blurred. No major complications, such as deep infection, osteomyelitis, hardware failure, or re-fracture, were observed during the follow-up period. Conclusion The Masquelet technique demonstrates favorable therapeutic effects on tibial and fibular bone defects resulting from severe gunshot wounds, and it represents a safe and reliable method for addressing such complex bone defects. However, given the small sample size and retrospective design of this study, further large-scale prospective studies are warranted to confirm these findings.